The Relationship Between Physical Activity, Fat and Carbohydrate Intake and Nutritional Status of Undergraduate Nursing Study Program Students at STIKes RSPAD Gatot Soebroto - P, F. Dwi Basuki; Yunita, Yunita; Atmaja, Elsa Mukti (JOURNAL EDUCATIONAL OF NURSING(JEN), 2024)
Nutritional status can be influenced by various factors including age, gender, and ethnicity. Nutritional status is also influenced by food intake and physical activity levels. Unbalanced nutritional intake can affect students' academic performance. Students who are malnourished tend to have low concentration, weak memory, and poor academic performance. This study aims to determine the relationship between Physical Activity, Fat and Carbohydrate Intake and Nutritional Status in Nursing S1 Students at STIKES RSPAD Gatot Soebroto. This study used an analytical observational research method using a cross-sectional design. Research Results: showed that there was no relationship between physical activity and the nutritional status of STIKes RSPAD Gatot Soebroto students known r = -0.179, there was no relationship between fat intake and student nutritional status known r = -648, and there was no relationship between carbohydrate intake and student nutritional status known r = 0.543.